The Influence of Financial Knowledge, Financial Attitude and Payment Gateway on The Financial Management Behavior of UIN North Sumatra Students - Lubis, Desi Indriani; Naution, Wendi Amsuri (SEIKO : Journal of Management & Business, 2024)
People in the age of the fifth industrial revolution need to be tech savvy in order to make good use of digital financial services for managing their money, given how quickly technology is advancing. Partially and simultaneously, this study intends to ascertain the impact of financial literacy, financial attitudes, and payment gateways on the financial management behavior of students. Quantitative research methods were employed in this investigation. A total of 83 students from UIN North Sumatra were polled using questionnaires to ascertain their financial literacy, attitudes, payment gateway use, and management practices. Multiple linear regression analysis is employed in the data analysis approach, which is executed using the IBM SPSS 22 data analysis tool. The study's findings disprove the hypothesis that students' financial management practices are unaffected by their level of partial financial literacy. At the same time, how students feel about money and the places they use to make payments impact how they handle their own finances. There is a positive and statistically significant relationship between students' actions in managing their own finances and their levels of financial literacy, attitude, and access to online payment systems. Keywords: financial knowledge; financial attitude; payment gateway; financial management behavior